Penerapan Model Pembelajaran Inquiry untuk Meningkatkan Pemahaman Konsep IPA di MTsN 1 Kepulauan Sula (Suatu Penelitian Tindakan Kelas) - Ipa, Rohani (Civiliza Publishing, Indonesia., 2024)
This research aims to improve the understanding of science concepts among students at MTsN 1 Kepulauan Sula through the application of the inquiry learning model. This Classroom Action Research was conducted in three cycles, with 29 eighth-grade students as research subjects. Data was collected through concept understanding tests, learning observations, and interviews. The results show an improvement in students' understanding of science concepts from cycle I to cycle III, with the class average score increasing from 65.8 to 78.5, and the percentage of students reaching the Minimum Competency Criteria increasing from 48% to 79%. Student activity in learning also showed improvement, evident from increased participation in group discussions, ability to ask questions, and formulate hypotheses. Challenges in applying the inquiry model, such as limited resources and adaptation to local context, were addressed through the use of local materials and contextualization of learning materials. This study concludes that the inquiry learning model, with appropriate adaptations, is effective in improving students' understanding of science concepts in Indonesia's outer island regions. These findings have important implications for efforts to improve the quality of science learning in similar areas.